E2 multimeric scaffold for vaccine formulation: immune response by intranasal delivery and transcriptome profile of E2-pulsed dendritic cells. Issue 1 (December 2016) - Trovato, Maria; Maurano, Francesco; D'Apice, Luciana; Costa, Valerio; Sartorius, Rossella; Cuccaro, Fausta; McBurney, Sean; Krebs, Shelly; Prisco, Antonella; Ciccodicola, Alfredo; Rossi, Mauro; Haigwood, Nancy; et al.
Abstract Background The E2 multimeric scaffold represents a powerful delivery system able to elicit robust humoral and cellular immune responses upon systemic administrations. Here recombinant E2 scaffold displaying the third variable loop of HIV-1 Envelope gp120 glycoprotein was administeredvia mucosa, and the mucosal and systemic immune responses were analysed. To gain further insights into the molecular mechanisms that orchestrate the immune response upon E2 vaccination, we analysed the transcriptome profile of dendritic cells (DCs) exposed to the E2 scaffold with the aim to define a specific gene expression signature for E2-primed immune responses. Results The in vivo immunogenicity and the potential of E2 scaffold as a mucosal vaccine candidate were investigated in BALB/c mice vaccinatedvia the intranasal route. Fecal and systemic antigen-specific IgA antibodies, cytokine-producing CD4+ and CD8+ cells were induced assessing the immunogenicity of E2 particlesvia intranasal administration. The cytokine analysis identified a mixed T-helper cell response, while the systemic antibody response showed a prevalence of IgG1 isotype indicative of a polarized Th2-type immune response. RNA-Sequencing analysis revealed that E2 scaffold up-regulates in DCs transcriptional regulators of the Th2-polarizing cell response, defining a type 2 DC transcriptomic signature. Conclusions The current study provides experimental evidence to the possible application of E2 scaffold as antigen delivery system for mucosal immunization and taking advantages of genome-wide approach dissects the type of response induced by E2 particles.